Self-Regulated Learning with a Module to Improve Learning Achievement - Ikhwanuddin Ikhwanuddin; Sumarjo H.; V. Lilik Hariyanto; A. Hasan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Drafting competence using Computer Aided Design (CAD) is required for building projects. The basic competence of CAD courses is students can draw elevation houses with CAD. To improve the effectiveness of learning, it has been developed a CAD learning module. This study was aimed to identify the utilization strategy of the CAD learning module to improve self-regulated learning. It is believed that increasing self-regulated learning can improve learning achievement. This research method consisted of four cycles: plan, action, observation, and reflection. The data were in the form of quantitative and qualitative data. Data collecting techniques were observation and documentation. Data analysis techniques used mean scores and reflection. The target was the mean score of classical tasks which is bigger than 80 in high difficult tasks. The results of the study were (1) there were differences in learning achievement in applying the concept of self-regulated learning with a collaborative approach and an individualistic approach, (2) self-regulated learning concepts with collaborative approach is more appropriate for the CAD module-based learning, and (3) the concept self-regulated learning with collaborative approach can improve learning achievement.